LED-pumped intense red luminescence based on Ba2LaTaO6: Mn4+ double perovskite phosphor. Issue 24 (15th December 2022) - Li, Liang; Cao, Qianwen; Wang, Jiajia; Li, Zhongyuan; Pan, Yan; Wei, Xiantao; Li, Yong
Abstract: Non-rare earth Mn 4+ ion-doped red oxide phosphors have great potential for applications in warm white light-emitting diodes (wLEDs) due to their low cost and stable physicochemical properties. Herein, a series of Ba2 LaTaO6 (BLTO): Mn 4+ phosphors were successfully synthesized by the high-temperature solid-state method. The theoretical values of the band gap calculated by the density functional theory are close to the experimental values obtained by the absorption spectroscopy. In addition, the phosphors have a broad excitation band in the wavelength range of 280–550 nm and emit red light at the peak wavelength of 681 nm under excitation. The concentration quenching of the BLTO: Mn 4+ phosphor was caused by dipole-dipole interactions. The activation energy and the average decay lifetimes of the samples were calculated. Meanwhile, the effects of synthesis temperature and Li + ion doping on the luminescence performance of the samples were also investigated. Satisfactorily, the color purity and internal quantum efficiency of the phosphor reached 98.3% and 26.8%, respectively. Further, the samples were prepared as red-light components for warm wLEDs. The correlated color temperature, color rendering index, and luminous efficiency of the representative devices driven by 60 mA current were 5190 K, 83.3, and 81.59 lm/W, respectively. This work shows that the BLTO: Mn 4+ red phosphor with excellent luminescence performance can be well applied to warm wLEDs. Graphical abstract: Emission spectra (left) and CIE chromaticity diagrams (right) of the blue LED-pumped warm wLEDs devices prepared with different ratios of the BLTO: 1.0 mol%Mn 4+ and YAG: Ce 3+ phosphors, driven at 60 mA. The inset shows a digital photograph of the prepared warm wLEDs device and its operation. Image 1